Challenges Hindering Academic Staff in Nigerian Tertiary Education from Securing Local and International Grants: A Descriptive Study: Tantangan yang Menghambat Staf Akademik di Pendidikan Tinggi Nigeria dalam Mendapatkan Hibah Lokal dan Internasional: Sebuah Studi Deskriptif - Ogunode, Niyi Jacob; D. M , Gregory (Universitas Muhammadiyah Sidoarjo, 2023)
This descriptive research aims to evaluate the perceptions of academic staff regarding the factors impeding their success in obtaining both local and international grants within Nigerian tertiary education. Employing a sample size of 240 participants from six federal universities spanning diverse geopolitical zones, a multistage sampling technique was applied. A bespoke questionnaire,